Advances in the Role of Leucine-Sensing in the Regulation of Protein Synthesis in Aging Skeletal Muscle - Zhao, Yan; Cholewa, Jason; Shang, Huayu; Yang, Yueqin; Ding, Xiaomin; Wang, Qianjin; Su, Quansheng; Zanchi, Nelo Eidy; Xia, Zhi (Frontiers in Cell and Developmental Biology, 2021)
Skeletal muscle anabolic resistance (i.e., the decrease in muscle protein synthesis in response to anabolic stimuli such as amino acids and exercise) has been identified as a major cause of age-related sarcopenia, to which blunted nutrition-sensing contributes. In recent years, it has been suggested that a leucine-sensor may function as a rate-limiting factor in skeletal muscle protein synthesis via small molecule GTPase. Leucine-sensing and response may therefore have important therapeutic potential in the steady regulation of protein metabolism in aging skeletal muscle. This paper systematically summarizes the three critical process involved in the leucine-sensing and response process:1) How the coincidence detector mammalian target of rapamycin complex 1 localizes on the surface of lysosome and how its crucial upstream regulators Rheb and RagB/RagD interact to modulate the leucine response; 2) How complexes such as Ragulator, GATOR, FLCN and TSC control the nucleotide loading state of Rheb and RagB/RagD to modulate their functional activity; 3) How the identified leucine sensor leucyl-tRNA synthetase (LARS) and stress response protein 2 (Sestrin2) participate in the leucine-sensing process and the activation of RagB/RagD. Finally, we discuss the potential mechanistic role of exercise and its interactions with leucine-sensing and anabolic responses.